CHALLENGES FOR ACCOUNTING PROFESSIONALS IN THE DIGITAL AGE IN INDONESIA - Nardi Gunawan; Ahmad Ahmad; Veri Muldani (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The accounting profession faces a threat in the form of ending accounting when the digital era emerges. This research then aims to see how the relationship exists between the technology of the accounting profession and strategies in the accounting profession during the digital era. This research will be carried out using a qualitative approach as well as data obtained from the results of previous research and studies that are still relevant. This study found that an accountant must adapt to this digitalization system in the digitalization era. The accountant profession also has new competitors, namely programmers and the technology it has in carrying out the work of the previous assistant. As for the academic field, accounting majors need to study information systems more actively to improve the accounting profession. In addition, learning from case studies also needs to be reproduced to provide creative thinking to make decisions so that the results can create an accountant profession that is ready in the digital era.